Penerapan Keselamatan Pasien Preoperasi dan Post Operasi di Rumah Sakit - Yongky Gousario; Henny A. Manafe; M. E. Perseveranda; Angreny Paridy (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research examines how the study of the implementation of pre-and post-operative patient safety in hospitals. The research used by researchers is a Systematic Literature Review with data obtained from journals and research articles from 2013-2023. The data source platforms used in this study are Google Scholar and PubMed. In this study, it is known that patient safety is an important health problem worldwide, and patient accidents in the operating room can cause serious problems. This miscommunication situation is a potential threat to patient safety because issues can easily go unnoticed by the rest of the team. Hospitals must provide a useful framework of requirements and safety protocols to address these challenges. One standard that can be used is the surgical safety checklist designed by WHO. The use of this list, in research, can increase safety procedurally, when surgery is performed, and after the action is given. Not only that, but hospitals must also provide formal instructions through various activities such as seminars, workshops, to conferences needed to increase awareness regarding patient safety before and after surgery.